Advances in the Optimization of Fe Nanoparticles: Unlocking Antifungal Properties for Biomedical Applications - Zeshan Ali Sandhu; Muhammad Asam Raza; Abdulmajeed Alqurashi; Samavia Sajid; Sufyan Ashraf; Kainat Imtiaz; Farhana Aman; Abdulrahman H. Alessa; Monis Bilal Shamsi; Muhammad Latif (MDPI AG, 2024)
In recent years, nanotechnology has achieved a remarkable status in shaping the future of biological applications, especially in combating fungal diseases. Owing to excellence in nanotechnology, iron nanoparticles (Fe NPs) have gained enormous attention in recent years. In this review, we have provided a comprehensive overview of Fe NPs covering key synthesis approaches and underlying working principles, the factors that influence their properties, essential characterization techniques, and the optimization of their antifungal potential. In addition, the diverse kinds of Fe NP delivery platforms that command highly effective release, with fewer toxic effects on patients, are of great significance in the medical field. The issues of biocompatibility, toxicity profiles, and applications of optimized Fe NPs in the field of biomedicine have also been described because these are the most significant factors determining their inclusion in clinical use. Besides this, the difficulties and regulations that exist in the transition from laboratory to experimental clinical studies (toxicity, specific standards, and safety concerns) of Fe NPs-based antifungal agents have been also summarized.